Convenient Reduction of Carbonyl Compounds with NaBH4/Wet Al2O3 System Under Solvent-Free, Solid-Gel and Microwave Irradiation - ZEYNIZADEH, BEHZAD; SETAMDIDEH, DAVOOD (Asian Journal of Chemistry, 2010)
Various carbonyl compounds such as aldehydes, ketones, α,β- unsaturated enals and enones, α-diketones and acyloins were reduced efficiently by NaBH4/wet Al2O3 system under solvent-free, solid-gel and microwave irradiation. The chemoselective reduction of aldehydes over ketones was achieved successfully by NaBH4/wet Al2O3 system at solvent-free condition.